IJCM_190A: A cross sectional study to find out risk factors for non-communicable diseases among residents of Raipur City, Chhattisgarh. - Chhediaha Vibha; Verma Nirmal; Jaiswal Prashant (Wolters Kluwer Medknow Publications, 2024)
Background: In India, due to high rates of urbanization and economic improvement, there is a shift in disease spectrum from communicable to non-communicable diseases. In a study made by khan etal 2015 at Bilapsur, Chhattisgarh prevalence of stroke was 67.6% due to infarct and 32.4 % had hemorrhage (ICH). The percentages of young stroke (< 45 yrs) were 12.5% (n=35). About 7.1% (n=20) and 5.3% (n=15) in males and females respectively. Thus, early detection will reduce the burden and cost of diseases in the family, community and on the nation. Objectives: A cross sectional study to find out risk factors for non- communicable diseases among residents of Raipur City, Chhattisgarh. Methodology: This is a cross-sectional study conducted in Raipur City of Chhattisgarh state during the month October 23-January 2024. A pre-designed, self-administered, semi-structured questionnaire was used for data collection. Systematic Random sampling technique was adopted to select the 350 Study participants. Results: The majority of subjects were between the ages of 30 and 40. Females constituted 55.3% of the subjects, while males accounted for 44.7%. Additionally, 45.6% of participants had completed primary schooling. Preobesity was observed in 58.8% of males and 51.7% of females.84.7% of study subjects were not engaging in physical activity, 89.1% were consuming an unhealthy diet, 97.6% were using tobacco, and 94.5% were consuming alcohol, all of which contributed to a raised BMI. There is a significant association between tobacco and alcohol use with BMI, where p-values are 0.001 and 0.005, respectively, which is <0.005 and df is 01 for both. Conclusion: As per this study, Pre-obese were found in 58.8% of males and 51.7% of females Awareness regarding healthy behavioral pattern and healthy diet should be inculcated in population through various awareness activity like mass media camping and increase taxes on unhealthy food items.